The Moderating Role of Psychological Essentialism in The Link Between Threat to Symbolic Purity and Exclusionary Attitudes Toward Foreigners - Akiko Matsuo; Hideya Kitamura; Shin-ichiro Kumagaya (Studia Psychologica)
Purity is a component of morality, which relates to perceptions of cleanliness (i.e., physical aspect) and divinity (i.e., symbolic aspect). Purity violations threaten one’s traditional values and beliefs and motivate people to recover purity by avoiding something atypical. Like the physical aspect of purity, violating the symbolic aspect of purity can lead people to recover the purity status by excluding out-group members. However, this link is possibly influenced by psychological essentialism, which is the degree of one’s perceptions about a clearly built boundary between social categories (e.g., men and women). Therefore, this study investigated the moderating role of essentialist beliefs in the relationship between purity-related morality in a symbolic sense and exclusionary attitudes toward foreigners. Two experimental studies were conducted in Japan, where immigrants play an essential role in securing the working-age population because of its recent “super-aged” situation. It was predicted that only lower essentialists would be sensitive to the threat, but not higher essentialists. The results did not support the hypothesis in the expected direction, but some valuable implications and suggestions for future research were made. In particular, this study revealed that symbolic purity may play a role in intergroup relations.